ANALISIS TANTANGAN YANG DIHADAPI GURU DALAM MEMBANGUN POLA KOMUNIKASI EFEKTIF PADA PEMBELAJARAN MATEMATIKA DI UPT SDN 004 SALO - Alayda, Nilmayati; Nurhaswinda; Ananda, Rizki; Rahma Sari, Afriza; Hana Pebriana, Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Effective communication between teachers and students is key to successful learning, especially in Mathematics, which requires a deep understanding of concepts. This study aims to analyze the challenges faced by teachers in developing effective communication patterns in Mathematics learning, identify influencing factors, and determine strategies implemented to improve them. This type of research is descriptive qualitative with five class teachers, fifteen students in grades III–V, and the principal as subjects. Data were collected through interviews, observation, and documentation, then analyzed through the processes of reduction, presentation, and drawing conclusions. The results show that the main challenges for teachers include differences in student learning abilities, lack of focus during learning, and the influence of gadget use. Factors that influence communication are teacher patience, language choice, and a conducive classroom atmosphere. Strategies used include a personal approach, educational games, and student involvement in learning. Overall, effective communication can be achieved through the application of five communication aspects according to Sukma et al. (2022): respect, empathy, audibility, clarity, and humility.